Strengthening CHED's developmental and regulatory capacity - Fernando T. Aldaba; Jose T. Sescon; Karl Eli Alconis (Philippine Institute for Development Studies (PIDS), 2024)
This paper examines and proposes strategies to strengthen the development and regulation of Higher Education in the Philippines as enacted by the Commission on Higher Education (CHED). Through a comprehensive review of CHED's mandate, a comparative analysis of higher education systems throughout Southeast Asia, and interviews with representatives from CHED and various Higher Education institutions, the study identifies strengths, weaknesses, and opportunities for improvement. Key issues faced include a disproportionate focus on regulation over development, challenges faced by universities in faculty capacity building, gaps in research and innovation support, and the misalignment of higher education curricula with board requirements and labor market demands. Drawing lessons from best practices throughout the region, the study recommends adopting a hybrid approach to foster equitable growth and innovation. Specific strategies include improving CHED's organizational efficiency by delineating regulatory and developmental functions, enhancing faculty development programs, and fostering partnerships between HEIs and industry to bridge the skills gap. The study also calls for improving university categorization, harmonizing accreditation standards among various accrediting bodies, strengthening internal quality assurance systems, and increasing financial support for underperforming but potential HEIs. By addressing these critical areas, CHED may better be able to fulfill its developmental and regulatory mandates.
Keywords: 330; higher education; CHED; regulatory capacity; developmental capacity; quality assurance; accreditation; faculty development; Southeast Asia; policy reform